2004
DOI: 10.1590/s1516-35982004000200014
|View full text |Cite
|
Sign up to set email alerts
|

Determinação dos valores energéticos de alguns óleos e gorduras para pintos de corte machos e fêmeas aos 21 dias de idade

Abstract: Foi realizado um ensaio biológico com pintos de corte no período de 21 a 32 dias de idade, com o objetivo de determinar os valores de energia metabolizável aparente (EMA) e energia metabolizável aparente corrigida pela retenção de nitrogênio (EMAn) do óleo de soja degomado, óleo de milho, óleo de canola, gordura de aves, gordura de coco, gordura suína, sebo bovino e de duas misturas, sendo a primeira composta de óleo de soja degomado + gordura de coco e a segunda de óleo de soja degomado + sebo bovino, ambas n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
1
4
0
6
Order By: Relevance
“…The metabolizable energy of corn oil (8,773kcal kg -1 ) approaches to soybean oil (8,790kcal kg -1 ; ROSTAGNO et al, 2011); in fact, NASCIF et al (2004) found that it is higher (corn oil: 8,666kcal kg -1 vs. soybean oil: 8,336kcal kg -1 ). BAIÃO & LARA (2005) reported additional values of 8,886kcal kg -1 (corn oil) and 8,790kcal kg -1 (soybean oil).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The metabolizable energy of corn oil (8,773kcal kg -1 ) approaches to soybean oil (8,790kcal kg -1 ; ROSTAGNO et al, 2011); in fact, NASCIF et al (2004) found that it is higher (corn oil: 8,666kcal kg -1 vs. soybean oil: 8,336kcal kg -1 ). BAIÃO & LARA (2005) reported additional values of 8,886kcal kg -1 (corn oil) and 8,790kcal kg -1 (soybean oil).…”
Section: Resultsmentioning
confidence: 99%
“…The oils and fats added to the diet of broilers greatly benefit their productivity; however, their use raises the final cost of feed (NASCIF et al, 2004). Nevertheless, corn oil (a by-product of the corn processing industry) has higher energy values than soybean oil (NASCIF et al, 2004;BAIÃO & LARA, 2005), and it is often extracted in large volumes by certain industries, resulting in a greater supply than demand.…”
Section: Animal Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os valores de EMA e EMAn obtidos para o óleo de soja refinado, o sebo bovino, a gordura de suínos e a gordura de aves foram superiores aos determinados por Nascif et al (2004), trabalhando com pintos de corte mistos (8.672 e 8.827 vs 8.394 e 8.389;7.486 e 7.641 vs 7.333 e 7.329;8.555 e 8.674 vs 7.624 e 7.619;8.600 e 8.720 vs 8.587 e 8.579 kcal/kg de MS,respectivamente).…”
Section: Resultsunclassified
“…Nevertheless, this ability develops quickly after the first days of life. (Table 3), which is dependent on the following factors: the length of the carbonic chain, the number of double bonds, the presence or absence of ester bonds (triglyceride or free fatty acid), the specific arrangement of the saturated and unsaturated fatty acids on the glycerol backbone, the composition of the free fatty acid, the composition of the diet, the type and quantity of triglycerides supplemented in the diet, the intestinal flora, the sex and age of the birds (Renner & Hill, 1961;Leeson & Summers, 2001, Nascif et al, 2004. Source: Adapted from Leeson & Summers (2001).…”
Section: Lipid Absorptionmentioning
confidence: 99%